A química e toxicidade dos corantes de cabelo - Oliveira, Ricardo A. G. De [UNESP]; Zanoni, Thalita B.; Bessegato, Guilherme G. [UNESP]; Oliveira, Danielle P.; Umbuzeiro, Gisela A.; Zanoni, Maria Valnice B. [UNESP] (Sociedade Brasileira de Química, 2014)
The market for hair dye involves a growing range of products, which requires greater understanding of hair properties, mechanisms of action and color development. In this work, we present a critical analysis of the classification, physical and chemical characteristics, chemical analysis and toxicological/mutagenic potential of dyes used in the hair dyeing process. A compilation of some studies was carried out, focusing on the available knowledge about these dyes and their effects on the environment and human health.
The chemistry and toxicity of hair dyes
Keywords: hair dyes; chemical analysis of hair dyes; toxicity of hair dyes